Optimization Improvement Using Pi Controller to Reach CCCV Method in Lead Acid Battery Load - Irianto; Rachma Prilian Eviningsih; Farid Dwi Murdianto; Amir Muhyidin (Universitas Muhammadiyah Malang, 2022)
Solar energy can produce electrical energy with the help of photovoltaics so as to produce sufficient or even excessive supply to the electrical load. Therefore, it is necessary to store electrical energy (battery) from the excess unused energy. However, in the process of charging the battery, it takes a long time to fully charge the battery capacity and damage often occurs due to excessive voltage used. This can reduce battery life. The characteristics of the battery need to be considered so that the charging process can be carried out in accordance with the required provisions. The existence of the CCCV method can speed up the battery charging process with a constant current of 20% of the nominal current of the lead acid battery. To avoid overvoltage, the constant voltage method can anticipate the occurrence of damage. Utilization CUK Converter as charging can reduce output voltage ripple. The PI control on the CUK Converter produces a constant voltage of 13.8 Volts and a constant current of 1.44 Ampere. The average error generated by this system is 0.14%.